Factors Affecting Donor Area Healing - Dr. Jagdish Sharma; Dr. B. S. Chandalia (Indian Journal of Plastic Surgery)
Split skin area healing was studied in 60 areas. The effect of various factors that in-fluence healing were also observed in the series. Superficial area dressed with antiseptic cream have gord quality healing. Deep donor area have more delayed healing with irregular areas of Hypertrophic scar.